Margem Esquerda 34 - Editor REA (Revista Espaço Acadêmico, 2020)
Título: Margem Esquerda 34Autores: Anselm Jappe, David Harvey, Michael Löwy, Tithi Bhattacharya, Noam Chomsky Páginas: 160ISBN: 9771678768400Ano de lançamento: 2020Editora: Boitempo